2002
DOI: 10.1161/01.cir.0000015700.27754.6f
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet Binding to Circulating Monocytes in Acute Coronary Syndromes

Abstract: Background — Present therapies for acute coronary syndromes aim toward limiting platelet–platelet adhesion and aggregation processes. However, platelet–leukocyte interactions may contribute importantly to disease progression in the arterial wall. Recent studies suggest that prevention of platelet–leukocyte binding via P-selectin glycoprotein ligand-1 (PSGL-1) may be beneficial in animal models of vascular injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
272
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(292 citation statements)
references
References 40 publications
(27 reference statements)
12
272
1
7
Order By: Relevance
“…For example, studies with un-separated leukocyte populations reveal a significant increase in platelet-leukocyte complexes in allergic mice and in human asthmatics (Pitchford et al, 2003(Pitchford et al, , 2005. Similar processes occur in patients with COPD (Ferroni et al, 2000), atherosclerosis (Arber et al, 1991;Ott et al, 1996;Neumann et al, 1997;Sarma et al, 2002;Huo et al, 2003) and RA (Joseph et al, 2001;Bunescu et al, 2004). In this regard, experimental models of disease have provided evidence for a requirement of platelets in pulmonary eosinophil and lymphocyte recruitment in rabbits, guineapigs and mice in models of allergic inflammation (LellouchTubiana et al, 1988;Coyle et al, 1990;Pitchford et al, 2003Pitchford et al, , 2005; and neutrophil and monocyte recruitment in atherosclerosis (Arber et al, 1991;Neumann et al, 1997;Hayward et al, 1999) and RA (Schmitt-Sody et al, 2005).…”
Section: Leukocyte Recruitment and Activation: Influence Of Plateletsmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, studies with un-separated leukocyte populations reveal a significant increase in platelet-leukocyte complexes in allergic mice and in human asthmatics (Pitchford et al, 2003(Pitchford et al, , 2005. Similar processes occur in patients with COPD (Ferroni et al, 2000), atherosclerosis (Arber et al, 1991;Ott et al, 1996;Neumann et al, 1997;Sarma et al, 2002;Huo et al, 2003) and RA (Joseph et al, 2001;Bunescu et al, 2004). In this regard, experimental models of disease have provided evidence for a requirement of platelets in pulmonary eosinophil and lymphocyte recruitment in rabbits, guineapigs and mice in models of allergic inflammation (LellouchTubiana et al, 1988;Coyle et al, 1990;Pitchford et al, 2003Pitchford et al, , 2005; and neutrophil and monocyte recruitment in atherosclerosis (Arber et al, 1991;Neumann et al, 1997;Hayward et al, 1999) and RA (Schmitt-Sody et al, 2005).…”
Section: Leukocyte Recruitment and Activation: Influence Of Plateletsmentioning
confidence: 96%
“…However, interactions between platelets and inflammatory cells take place during atherosclerosis and this stimulation of an inflammatory response within the atherosclerotic plaque may trigger acute coronary events via reactive oxygen species (ROS) production and MMP secretion (Poubelle and Borgeat, 2002). Substantial clinical evidence demonstrates activation of circulating platelets in diseases with a substantial inflammatory component acting on the vasculature, for example, acute coronary syndromes such as myocardial infarction and unstable angina (Sarma et al, 2002) and atherosclerosis (Massberg et al, 2002). These studies suggest a participation of platelets in the inflammatory responses as well as the recognized events leading to thrombus formation.…”
Section: Platelet Activation In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…15 In addition, despite blocking the glycoprotein IIb/IIIa receptor with tirofiban, platelets can activate white cells via their P-selectin receptor which binds to P-selectin glycoproteinligand-1 on leukocytes. 16 The clinical and angiographic characteristics of the population studied may also be an importantreason for the absence of anti-inflammatoryeffect. Because of the proven benefit of anti-glycoprotein IIb/IIIa receptor blockade in unstable patients, it was not ethical to withhold tirofiban treatment on such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet MPs expose platelet-specific antigens on their surface and can adhere to leukocyte in a P-selectin dependent manner [7]. Clinical studies have shown that elevated levels of microparticles were found in patients with disseminated intravascular coagulation [13], unstable angina [14], myocardial infarction [15,16], coronary angiography [17], transient ischemia attacks [18], and diabetes mellitus [19]. A deficiency of platelet MP generation can result in a bleeding disorder characterized with prolonged bleeding time [20].…”
Section: Introductionmentioning
confidence: 99%